Constructing classes and imagining buildings: urban renewal and transactions between concepts and materialities in Mumbai - Holwitt, Pablo (Antipode)
This paper deals with multi-directional transactions between concepts and materialities in contemporary processes of urban renewal. Building upon insights gained from debates about the nature of materialities within urban geography, I treat buildings as complex associations of materials, technologies and human beings that are informed by concepts about social stratification and that simultaneously enact these concepts in the physical-social landscape of the city. Processes of urban renewal therefore need to be understood as both conceptual and material interventions in the setup of the city that restructure the built environment, patterns of cohabitation, experiences of the urban and notions of self and other. I illustrate this approach with recourse to the case of urban renewal in the city centre of Mumbai, arguing that high-rise buildings emerging from urban redevelopment projects translate the heterogeneity of the Indian middle classes into a spatial vocabulary that contributes to the creation of new social categories.